2022
DOI: 10.1186/s12886-022-02622-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of high-intensity focused ultrasound cyclo-plasty in glaucoma

Abstract: Background High-intensity focused ultrasound cyclo-plasty (UCP) is a recently developed glaucoma surgery. This study collected and analysed the clinical data of patients who underwent UCP to observe the efficacy and safety of this surgery in Chinese glaucoma patients. Methods This was a retrospective study. The clinical data of all the patients who underwent UCP at Affiliated Foshan Hospital, Southern Medical University, were collected and analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Chen and Guo treated 61 eyes (7 POAG, 17 PACG, 26 NVG, 11 secondary glaucoma) with UCP and followed up for 18 months and found that IOP reduction was more than 60% at 1 month after UCP, and more than 30% 18 months after UCP, with a success rate of 94. 55% at 7 days after UCP, and more than 60% 18 months after UCP [13]. We did a correlation analysis and found that that there was a signi cant linear correlation between the decrease in postoperative intraocular pressure and preoperative intraocular pressure.…”
Section: Discussionmentioning
confidence: 81%
“…Chen and Guo treated 61 eyes (7 POAG, 17 PACG, 26 NVG, 11 secondary glaucoma) with UCP and followed up for 18 months and found that IOP reduction was more than 60% at 1 month after UCP, and more than 30% 18 months after UCP, with a success rate of 94. 55% at 7 days after UCP, and more than 60% 18 months after UCP [13]. We did a correlation analysis and found that that there was a signi cant linear correlation between the decrease in postoperative intraocular pressure and preoperative intraocular pressure.…”
Section: Discussionmentioning
confidence: 81%